Natural and Induced Antibody Polyreactivity - Jarossay, Annaelle; Hadzhieva, Maya; V. Kaveri, Srinivas; Lacroix-Desmazes, Sebastien; D. Dimitrov, Jordan (Anti-Cancer Agents in Medicinal Chemistry, 2015)
Healthy immune repertoire contains a fraction of immunoglobulins that do not possess exquisite antigen specificity but are able to recognize numerous unrelated antigens with similar values of the binding affinity. These antibodies are referred to as polyreactive. Besides natural polyreactive antibodies immune repertoires contain antibodies that acquire polyreactivity post-translationally, upon structural changes in their variable regions. In this article we made an overview of the recent findings about antibody polyreactivity. After introduction of the concept, and description of the origin, functions, and molecular mechanisms of polyreactive antibodies, we discussed their role in autoimmunity, malignancy and infectious diseases. We made a parallel with similar data about antibodies with induced polyreactivity. This review highlights the importance of natural and acquired antibody polyreactivity in immune defense and surveillance and reveals their potential as a new type of therapeutics.
Keywords: autoimmunity